Psychological Well-Being Pada Pasien Diabetes Melitus Yang Menjalani Rawat Inap - Dwin Seprian; Nurul Hidayah; Masmuri Masmuri (Institut Citra Internasional, 2023)
Long-term treatment for diabetes mellitus (DM) patients makes it difficult to control blood sugar effectively, causing patients to experience biological, psychological, social, and spiritual imbalances. One of the psychological aspects of impact on patients with diabetes mellitus is Psychological Well Being (PWB). Psychological Well Being is a measure to see whether an individual can accept himself as a whole. DM patients who have a low PWB will have an impact on low levels of self-care. This study aims to determine the description of Psychological Well Being in diabetes mellitus patients who are hospitalized. This research method uses a quantitative descriptive survey with a cross-sectional approach. The sampling technique used non-probability sampling with a total sampling technique of 60 respondents. The results of the Psychological Well-Being study were low for 3 respondents (5.0%), medium for 54 respondents (90.0%), and high for 3 respondents (5.0%). Inpatient diabetes mellitus patients who have Psychological Well-Being in the moderate category still need to get more attention because other indicators might cause negative Psychological Well-Being.